2016
DOI: 10.1680/jgeot.15.t.035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle shape on small-strain damping ratio of dry sands

Abstract: This study reports on the significance of particle shape on the small-strain damping ratio of dry sands in shear (D s,min ) through a comprehensive set of torsional resonant column tests. Sands with a variety of grain shapes prepared at variable initial densities are studied. The samples are subjected to torsional resonant column tests under isotropic confining pressures ( p′) ranging from 50 to 800 kPa. Small-strain damping ratios are derived based on the free-vibration decay mode of the samples and the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 11 publications
2
17
1
Order By: Relevance
“…Giang et al (2017) obtained the sphericity of a calcareous sand and Mol sand by X-ray tomography and they found the sphericity of the calcareous sand is lower than that of the Mol sand. Research conducted by Payan et al (2016) and Giang et al (2017) reveal that sands with lower sphericity are stiffer due to the stronger intercontact and rotation resistance between particles. In addition, a lot of research has been carried out on the effect of mean grain size (D 50 ) and the coefficient of uniformity (C u ) on the smallstrain stiffness of sands and it has been demonstrated that C u is an important factor affecting the small-strain stiffness, while the effect of D 50 is insignificant (Iwasaki & Tatsuoka, 1977;Wichtmann & Triantafyllidis, 2009, 2010Enomoto, 2016;Payan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giang et al (2017) obtained the sphericity of a calcareous sand and Mol sand by X-ray tomography and they found the sphericity of the calcareous sand is lower than that of the Mol sand. Research conducted by Payan et al (2016) and Giang et al (2017) reveal that sands with lower sphericity are stiffer due to the stronger intercontact and rotation resistance between particles. In addition, a lot of research has been carried out on the effect of mean grain size (D 50 ) and the coefficient of uniformity (C u ) on the smallstrain stiffness of sands and it has been demonstrated that C u is an important factor affecting the small-strain stiffness, while the effect of D 50 is insignificant (Iwasaki & Tatsuoka, 1977;Wichtmann & Triantafyllidis, 2009, 2010Enomoto, 2016;Payan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Payan et al (2016) and Giang et al (2017) reveal that sands with lower sphericity are stiffer due to the stronger intercontact and rotation resistance between particles. In addition, a lot of research has been carried out on the effect of mean grain size (D 50 ) and the coefficient of uniformity (C u ) on the smallstrain stiffness of sands and it has been demonstrated that C u is an important factor affecting the small-strain stiffness, while the effect of D 50 is insignificant (Iwasaki & Tatsuoka, 1977;Wichtmann & Triantafyllidis, 2009, 2010Enomoto, 2016;Payan et al, 2016). The research presented above indicates that the investigation of the small-strain stiffness anisotropy of sandy soils, taking the particle characteristics and gradation into consideration, is interesting and worthwhile, especially for calcareous sand with a morphology of low sphericity, as reported by Giang et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Payan et al . [ 34 ] studied the effect of particle shape on the damping ratio of soils due to free vibration and developed an expression for the damping ratio of soils subjected to confining stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, a complete characterization of the constitutive behavior of geological materials necessitates their examination at multi-scales, including the interactions between grains (i.e., micromechanical response) and the influence of these interactions on the bulk behavior of “granular” systems. For example, previous studies on granular materials have shown a strong dependency of their mechanical response as bulk systems, on the interparticle friction [ 29 , 30 , 31 , 32 , 33 ] and the properties/characteristics of individual grains such as roughness, shape and strength/mode of failure, which influence the energy dissipation mechanisms and the resistance against shearing-induced strains [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Multi-scale insights of granular systems can provide a framework to understand the load transfer mechanisms and the flow behavior of particulate materials at a fundamental level [ 36 , 37 , 38 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], which are strongly linked to the properties at the grain-scale.…”
Section: Introductionmentioning
confidence: 99%